Karakterisasi Pasta Gigi Berbahan Abrasif Hidroksiapatit (HAp) - Agung Rimayanto Gintu; Elizabeth Betty Elok Kristian; Yohanes Martono (Jurnal Kimia Riset, 2020)
Tootpaste was a product for dental care to clean, beautify and replace the minerals decay from the dent surface. To prevent the damage of the mineral layers on the surface, added the remineralitation compounds in the formula of the toothpaste. The remineralitation agents commonly add was CaCO3 and CaPO4, during the technological development the calcium compounds added was calcium in nano size like Hydroxyapatite (HAp). In this study produced the contains abrasive HAp and CaCO3 with the mix ratio  CaCO3, 50:50 (HAp:CaCO3) and HAp. The characterization to the toothpaste with CaCO3 abrasive showed the Calcium contains 21,10 ± 0,0577%; dispersibility 936,37 ± 39,42gcm/s; pH 8,3 ± 0,00; and viscosity 25 ± 0,00 P.a. The toothpaste with CaCO3:HAp (50:50) abrasive showed the Calcium contains 27,03 ± 0,0333%; dispersibility 931,93 ± 22,62gcm/s; pH 8,8 ± 0,00; and viscosity 27 ± 0,00 P.a. The toothpaste with HAp abrasive showed the Calcium contains 27,67 ± 0,0882%; dispersibility 987,33 ± 39,50gcm/s; pH 8,9 ± 0,00; and viscosity 27,5 ± 0,00 P.a. The contamination of microbiology did not found in all of the toothpastes along the storage. Based on the entire organoleptic test against the toothpastes, the formula of toothpaste with the mix of CaCO3:HAp was les liked.